The fruits of freedom in British Togoland : literacy, politics and nationalism, 1914-2014 - Skinner, Kate (Katharine Alexandra Collier) (African studies series., 2015)
The Fruits of Freedom in British Togoland examines the history and politics behind the failed project of Togoland unification.